Estado nutricional y el nivel socioeconómico de los niños en edad escolar de 6-11 años de edad del distrito de quiruvilca de la provincia de Santiago de Chuco - La Libertad octubre - diciembre 2016 - Cueva Bacilio, Martín Eusebio (2017)
The nutritional status of an individual is a result of the balance or imbalance between the consumption of food and the respective use of nutrients to meet the requirements of these by the body according to age, sex, physiological state and physical activity. The term malnutrition encompasses nutritional states such as: malnutrition and obesity. Both conditions are the result of an imbalance between the bodily necessities and the consumption of essential nutrients; as well as the socioeconomic level of the families also intervenes in the nutritional status of children. Objective: To determine the nutritional status and socioeconomic status of children aged 6-11 years of the Quiruvilca District of the Province of Santiago de Chuco - La Libertad October - December 2016, using anthropometric parameters and a survey for the socioeconomic level. Material and Methods: Descriptive cross-sectional study of 266 school-age children. Results: We found 1.2% with malnutrition, 81.2% normal and 0.6% overweight; 18.8% of low stature and 16.9% of low and normal stature risk 62%; 28.2% with socioeconomic level I, 63.5% with socioeconomic level II and 8.3% with socioeconomic level III. Conclusions: We found a low number of children with malnutrition according to the BMI indicator, height for age and socioeconomic status